Study of Complexation Behaviour of Lignite Extracted Humic Acid with Some Divalent Cations - Iqbal, Pervez; Aftab , Kiran (The Indonesian Institute of Science and Technology Research, 2023)
In biogeochemical cycles, humic substances are natural electron shuttles in transforming nutrients and environmental pollutants. Humic acid complexes with macro and micronutrient metals are eco-friendly organo-mineral fertilisers. This study prepared and characterised lignite-extracted humic acid-metal (Fe, Mg, Zn) complexes. The proximate analysis exhibited the moisture, volatile matter, ash and fixed carbon contents of extracted humic acid of 02.61%, 17.31%, 57.18% and 22.90%, respectively. The percentage of metal ions in humic acid complexes ranges from 3.5-7.25%. The FTIR analysis of coal-extracted humic acids-metal complexes showed Zn, Mg and Fe ions complexed in a bidentate manner predominantly with the carboxylic acid moiety of humic acid. Thermal gravimetric analysis indicated a higher value of humic acid decomposition than their metal complexes. The thermal stability observed order is HA- Zn >HA-Fe>HA- Mg. The X-ray diffraction pattern pointed toward the noncrystalline nature of humic acid and their respective complexes due to having few intense and small diffuse peaks in the 2θ range from 0 to 80°. Hence, the humic acid-metals complexes increase the soil humic content and the availability of essential nutrients that enhance the loam's biotic action.